Peningkatan Hasil Belajar IPS dengan Menerapkan Literasi Digital pada Pelajar Kelas 8 B SMP Negeri 16 Jakarta - Isna Nur’aini; Budiaman; Dian Alfia Purwandari (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
This research is aimed at elevating the learning outcomes in Social Studies for the 8B class of SMP Negeri 16 Jakarta by integrating digital literacy into the students' curriculum. Employing a Classroom Action Research method, the study spanned three cycles, involving 35 students from the aforementioned class. Conducted from March to May 2024 at SMP Negeri 16 Jakarta, data collection included observation, testing, and documentation. Results revealed a significant enhancement in student academic performance through the implementation of digital literacy in Social Studies instruction. Analysis across cycles demonstrated consistent improvement in learning mastery, with percentages escalating from 62.85% in the first cycle to 77.14% in the second, and ultimately reaching 85.71% in the third cycle. Beyond academic achievement, the integration of digital literacy fostered active student engagement in the learning process. Students participated more vigorously in discussions, shared information, and adeptly utilized technology to access learning resources. This underscores the dual role of digital literacy: not only as a means of information retrieval but also as a tool for fostering deeper student engagement. Consequently, these findings offer valuable insights for enhancing educational quality, particularly in leveraging digital technology to facilitate more effective and interactive learning experiences.